Preoperative colonization in pediatric cardiac surgery and its impact on postoperative infections. Issue 8 (15th May 2017) - Silvetti, Simona; Ranucci, Marco; Isgrò, Giuseppe; Villa, Valentina; Costa, Elena
Summary: Background: Patients with congenital heart defects are frequently hospitalized before surgery. This exposes them to a high risk for pathogen colonization. There are limited data on colonization prevalence in the pediatric cardiac population, and limited data concerning its potential role in the risk of developing infections after cardiac surgery. Aim: This study aimed to verify the impact of preoperative colonization on postoperative infections in a population of pediatric cardiac surgery patients coming from Italy and developing countries. Methods: This was a retrospective study conducted in all the patients aged ≤18 years who underwent pediatric open‐heart surgery in the year 2015. Clinical data were retrieved from the institutional database for cardiac surgery patients. Data on swab cultures were retrieved from the laboratory database. Swab colonization was tested for association with infection and other outcomes. Results: Among 169 children who performed the screening for pathogen colonization, 50% had at least one positive swab. Italian patients were ( P =.001) less likely to be colonized with respect to foreign patients (relative risk 0.17, 95% CI 0.09‐0.35). Postoperative infections in colonized patients occurred at a similar rate as in noncolonized patients (relative risk 1.24, 95% CI 0.64‐2.39; P =.532). Colonized patients had a preoperative stay ( P =.021) longer than noncolonized patients (mean difference 2 days, 95% CI 0.3‐3.8 days). Conclusion: The results of our study suggest that the impact of preoperative colonization on outcome and postoperative infections may be negligible; larger series are required to clearly define this issue.